A revision of Ledebouria (Hyacinthaceae) in South Africa. 1. Two new species - S. Venter; T. J. Edwards (Bothalia: African Biodiversity & Conservation, 1998)
A revision of Ledebouria in South Africa has revealed a number of undescribed species. This paper deals with two new species,  Ledebouria atrobrunnea S.Venter and L dolomiticola S.Venter. Both species possess cylindrical bulbs, erect leaves (rare in Ledebouria) and prominent shoulders on the carpel apices. These synapomorphies are also seen in L viscosa Jessop, and its allies.